The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ijfs.13063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emulsifier type on physicochemical properties of water‐in‐oil emulsions for confectionery applications

Abstract: Summary In a first step of designing tailored confectionery masses using water‐in‐oil emulsions, a parameter screening on emulsion rheology and stability was carried out. The experimental set‐up included cocoa butter as continuous phase and the variation of the disperse phase (water, or 50% sucrose in water), two volume fraction levels and the type of emulsifier (lecithin, polyglycerol polyricinoleate (PGPR), ammonium phosphatide (YN) and blends of lecithin or YN with PGPR). Emulsions were characterised by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Similar microstructures have been reported in literature for w/o emulsions stabilised with lecithin, sorbitan esters or sucrose esters dissolved in sunflower oil or olive oil as the continuous emulsion phase (Balcaen et al, 2017;Mazo Rivas et al, 2016;Ushikubo & Cunha, 2014). According to Ushikubo and Cunha (2014) and Mazo Rivas et al (2016), the formation of droplet aggregates in sucrose ester stabilised w/o emulsions can be attributed to the self-assembly of the sucrose ester molecules dissolved in oil forming an entangled dynamic network and thus promoting aggregation in oil-based emulsions. Nevertheless, the aggregates could be somewhat disintegrated by shearing on a magnetic stirrer as evidenced in Fig.…”
Section: Primary W 1 /O Emulsion Designsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar microstructures have been reported in literature for w/o emulsions stabilised with lecithin, sorbitan esters or sucrose esters dissolved in sunflower oil or olive oil as the continuous emulsion phase (Balcaen et al, 2017;Mazo Rivas et al, 2016;Ushikubo & Cunha, 2014). According to Ushikubo and Cunha (2014) and Mazo Rivas et al (2016), the formation of droplet aggregates in sucrose ester stabilised w/o emulsions can be attributed to the self-assembly of the sucrose ester molecules dissolved in oil forming an entangled dynamic network and thus promoting aggregation in oil-based emulsions. Nevertheless, the aggregates could be somewhat disintegrated by shearing on a magnetic stirrer as evidenced in Fig.…”
Section: Primary W 1 /O Emulsion Designsupporting
confidence: 82%
“…This difference in behaviour between sucrose ester and PGPR has previously been reported by Balcaen et al (2017) suggesting that the polymeric side chain of a PGPR molecule compared to the monomeric side chain of a sucrose ester might be responsible. In any case, PGPR is a well-known emulsifier for w/o emulsions, imparting long-range steric forces and repulsive barriers between adjacent droplets overcoming classical emulsion droplet instability phenomena such as droplet coalescence and flocculation/aggregation (Mazo Rivas et al, 2016;Middendorf et al, 2015). Another observation was that the PGPR stabilised droplets were much smaller than the SE O-170 stabilised droplets, so small indeed that it is not possible to ascertain whether the emulsion processed with the Silverson (Fig.…”
Section: Primary W 1 /O Emulsion Designmentioning
confidence: 99%
“…(2021) have revealed that the concentration of PGPR required to produces stable W/O emulsions can be greatly reduced by combining PGPR with a similar quantity of lecithin in the oil phase. In emulsifier blends (e.g., blends of PGPR with lecithin), PGPR is mainly responsible for modulating the physical characteristics of the emulsions (Mazo Rivas et al., 2016); these emulsions show a shear thinning behavior and a high viscosity at low shear rate (Okuro et al., 2019). These results also revealed that the ideal PGPR: Lecithin ratios were discovered to be 1.5:0.5 and 1.0:1.0, resulting in emulsions with superior kinetic stability because of the formation of an improved viscoelastic interfacial layer.…”
Section: Functional Properties Of Pgprmentioning
confidence: 99%
“…Obtained research results confirmed that the bench‐scale margarine line was a powerful device to produce cocoa butter emulsions, and that the desired physical property of W/O emulsions could be obtained by modifying the processing conditions such as shearing, emulsification temperature and residence time. Similarly, Mazo Rivas, Schneider, and Rohm () have used W/O emulsion to design tailored confectionery masses. The W/O emulsions set cocoa butter as a continuous phase and 50% sucrose in water as the dispersed phase.…”
Section: Application Of W/o Emulsionsmentioning
confidence: 99%